My Fight for a New Taiwan : One Woman's Journey from Prison to Power - Lü, Xiulian (Book collections on Project MUSE., 2014)
Lu Hsiu-lien's journey is the story of Taiwan. Through her successive drives for gender equality, human rights, political reform, Taiwan independence, and, currently, environmental protection, Lu has played a key role in Taiwan's evolution from dictatorship to democracy. Her impoverished parents twice attempted to give her away for adoption, and as an adult, she survived cancer and imprisonment, later achieving success as an elected politician--the first self-made woman to serve with such prominence in Asia.